Reflections on the contemporary moment in South Africa: art publics, art money, and art objects at Joburg Art Fair, 2008-2009 - Labuscagne, Cobi (My University, 2011)
This study is aimed at understanding recent changes in the social and economic landscape of South Africa in this contemporary moment. The field within which these changes are monitored is that of the Joburg Art Fair 2008 and 2009. The Joburg Art Fair, positioned as a corporate art sponsorship endeavor that attempts to bridge the realms of contemporary African art and commerce, speaks to aspects in the social and economic fields of South Africa beyond the case itself. A close reading of the event, through key actors, publics, and institutions throws into relief a moment in the South African art market which suggests the circulation of money, art works and notions of aesthetics and value. The event also highlights particular anxieties about the present in South Africa, while, through the language of hype and speculation, speaks of the hopes and ideals for the country’s present and future. Three different ‘lenses’ are used to read this field: that of the social to understand the ‘publics’ of this event; that of the cultural economic to investigate how such an event comes to exist at this time; and that of the aesthetic through which art works are read as markers of the contemporary moment. Moreover, the study asks ‘In what ways do art publics, art money and art works in the field of visual contemporary art production, reflect and produce a public culture in contemporary South Africa